An experimental and theoretical investigation of the structural behaviour of cross-bracing in transmission line steel towers - Behncke, Roberto Hector (My University, 2016)
This thesis presents the results of theoretical and experimental investigations into the behaviour and ultimate load capacity of latticed lower panels with cross-bracing diagonals made of equal-leg, hot-rolled steel angles under the effects of in-plane loads. Loading tests to collapse are carried out on cross-bracings in reduced-scale two-dimensional frames of various arrangements. The Southwell-plot of deflection measurements immediately prior to first yield of the diagonals is used to define equivalent end eccentricities and effective length factors, which therefore account for geometric and material imperfections of the test specimens. A proposal for new design formulae for calculating the resistance of struts is presented. The new design equations are based on the secant formula and are calibrs"ed against the experimental results. A computer model is developed based on flexibility equations which do not require an narative analysis procedure. The non-linear effects are given through the inclusion of Berry stability functions. The effects of eccentric forces and nodal restraints are simulated at all joints in which diagonals and main chords are connected . An additional model is formulated using a mainframe finite-element cod, demonstrating that it is now possible to perform non-linear analyses of complex frames including asymmetric members. Experimental results from this and other investigations are compared with ultimate load predictions based on the new design equations and the computer models and also usual buckling curves for design of steel transmission towers. In all cases the proposed models give acceptable predictions ot the behaviour and ultimate capacity of the bracings. In particular, failure loads calculated with the new design equations show improvements with respect to predictions based on current design buckling curves. These equations, therefore, can be used for design of steel latticed tower structures with angle members.
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 1992.
Keywords: Structural analysis (Engineering); Structural design.; Load factor design.; Structural dynamics.; Strains and stresses.